2021
DOI: 10.3390/mi12030307
|View full text |Cite
|
Sign up to set email alerts
|

Design of Customize Interbody Fusion Cages of Ti64ELI with Gradient Porosity by Selective Laser Melting Process

Abstract: Intervertebral fusion surgery for spinal trauma, degeneration, and deformity correction is a major vertebral reconstruction operation. For most cages, the stiffness of the cage is high enough to cause stress concentration, leading to a stress shielding effect between the vertebral bones and the cages. The stress shielding effect affects the outcome after the reconstruction surgery, easily causing damage and leading to a higher risk of reoperation. A porous structure for the spinal fusion cage can effectively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Differences in elastic moduli between the implant and bone cause stress shielding, finally leading to the weakening of the bone ( Murr, 2020 ). In cases of osteoporotic or osteopenia, a porous cage with one standard modulus may not a suitable choice due to the differences in the moduli ( Li et al, 2019 ; Pan et al, 2021 ).…”
Section: Biomechanically-matched Ep-vbmd Interbody Cage Developmentmentioning
confidence: 99%
“…Differences in elastic moduli between the implant and bone cause stress shielding, finally leading to the weakening of the bone ( Murr, 2020 ). In cases of osteoporotic or osteopenia, a porous cage with one standard modulus may not a suitable choice due to the differences in the moduli ( Li et al, 2019 ; Pan et al, 2021 ).…”
Section: Biomechanically-matched Ep-vbmd Interbody Cage Developmentmentioning
confidence: 99%
“…The results show that the average Young's coefficient for the original specimen before annealing was 126.44 GPa and the average hardness value was 3.9 GPa, as shown in Figure 16a. However, these values are lower than those of the annealed specimens, as shown in Figure 16b, with an average Young's coefficient of 131.46 GPa and an average hardness value of 4.12 GPa, which confirmed that the average Young's modulus and the average hardness could be increased after annealing treatment due to the removal of residual stress [22,26]. A comparison of the data is shown in Table 9.…”
Section: Ti-6al-4v Combined With Hap Materials For Pore Gradient Composite Scaffold Designmentioning
confidence: 74%
“…Therefore, to improve the mechanical properties, and maximizing biological properties, creating a graded/gradient porosity structure is one of the most effective solutions. [216][217][218][219] The design pattern of these implants imitates bone structure. The bone has a functionally graded structure where the outer part, called cortical, which is dense and has a modulus of elasticity is B15-25 GPa, the inner part is called trabecular with a porous structure and its modulus of elasticity is B0.1-4.5 GPa.…”
Section: 114mentioning
confidence: 99%